The Making of Margot Tony Palmer talks about his new film - Craine, Debra (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Tony Palmer talks about his new film. PALABRAS CLAVE: Tony Palmer, Margot Fonteyn, The South Bank Show.